Effect of Bacillus sp. Supplementation Diet on Survival Rate and Microbiota Composition in Artificially Produced Eel Larvae (Anguilla japonica) - Jang, Won Je; Kim, Shin-Kwon; Lee, Su-Jeong; Kim, Haham; Ryu, Yong-Woon; Shin, Min Gyu; Lee, Jong Min; Lee, Kyung-Bon; Lee, Eun-Woo (Frontiers in Microbiology, 2022)
This study was performed to investigate the effect of microbial supplementation diet on the survival rate and microbiota composition of artificially produced eel larvae. Microorganisms supplemented in the diet were isolated from wild glass eel intestines and identified as Bacillus sp. through 16S rRNA sequencing analysis. In vitro tests confirmed that the strain had no hemolytic activity and virulence genes. Microbial supplemental feeding significantly increased the survival rate of artificially produced eel larvae for 30 days post-hatchling compared with that of the control group. It also caused changes in the α-diversity, β-diversity, and relative abundance of the bacterial communities. Analysis via phylogenetic investigation of communities by reconstruction of unobserved states predicted that these microbial community changes would significantly increase the carbohydrate metabolism, membrane transport, and cellular community pathway of the microbial supplementation group. Therefore, microbial supplementation feeding for eel aquaculture could increase the viability of artificially produced eel larvae and alter the microbial composition to induce metabolic changes.